Analisa Dampak Disrupsi pada Permasalahan Spare Part Joint Replenishment - Erly Ekayanti Rosyida; Erik Ricardo; Dwi Iryaning Handayani (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to minimize inventory costs by implementing a joint replenishment policy on the spare parts inventory system by considering disruption. Analysis was carried out on 11 spare parts related to the effect of disruption on the determination of T, kj and the total costs generated. The results showed that the implementation of joint replenishment policy can reduce inventory costs by up to 21.7%. The effect of disruption in the form of rising material prices affects the increase in total costs linearly. Based on this, companies can choose the right time to order spare parts inventory, so as to avoid excessive storage costs and ordering costs.